1994
DOI: 10.1017/s0021859600067307
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and position of the shoot apex in some temperate grasses

Abstract: S U M M A R YThe morphology and position of the shoot apex in field swards was studied in 12 grasses for 12 months, in eight related grasses in 2 years, and in seedlings, young tillers and older tillers of Lolium perenne.Lolium multiflorum had relatively large numbers of primordia, long apices, which were above ground or near ground level, and a small length of apex per primordium. Festuca arundinacea had few primordia, a large length of apex per primordium, and apices which were well below ground or near grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Control (irrigated) plants were sampled on days 26 and 73 only. Following rewatering on day 82, plants were sampled after 1, 2, 5 and 8 d. As the position and the protection of the shoot apex could be among the most important factors affecting the persistence of a grass species (Wilman, Gao & Michaud, 1994), we measured the position of the meristems (i.e. depth in the soil for cocksfoot and length of aerial tillers for ryegrass) on days 3, 26 and 48 after the last irrigation.…”
Section: Position and Water Relations Of Leaf Basesmentioning
confidence: 99%
“…Control (irrigated) plants were sampled on days 26 and 73 only. Following rewatering on day 82, plants were sampled after 1, 2, 5 and 8 d. As the position and the protection of the shoot apex could be among the most important factors affecting the persistence of a grass species (Wilman, Gao & Michaud, 1994), we measured the position of the meristems (i.e. depth in the soil for cocksfoot and length of aerial tillers for ryegrass) on days 3, 26 and 48 after the last irrigation.…”
Section: Position and Water Relations Of Leaf Basesmentioning
confidence: 99%
“…Some differences as possible about their herbage production potential, between these grasses in morphology and development rate of establishment and persistence. However, most have already been reported ; of the emphasis on grass evaluation, as in the work of Wilman et al 1994). The present paper considers the National Institute of Agricultural Botany (1994) differences in herbage production and tiller density, in England and Wales, has been on comparisons of cultivars within species, rather than on comparisons M A T E R I A L S AND M E T H O D S of species, hybrids and mixtures.…”
Section: The Selection Of Grass Species Hybrids and Mixturesmentioning
confidence: 99%
“…Interspecific variation in numbers of leaf primordia immediately below the apical meristem has been previously reported (Sharman 1947;Wilman et al 1994), and the latter authors also found a higher number of pre-emergent leaves and primordia in ryegrass than in tall fescue. Similarly, the increase in undeveloped primordia under more severe defoliation seems consistent with reports of accumulation of undeveloped primordia during periods of moisture deficit stress (D. J. Barker pers.…”
Section: Phytomer Developmental Sequencementioning
confidence: 54%
“…Data on numbers of phytomers in an entire tiller axis would clearly be a key component in any mechanistic model describing tiller behaviour on the basis of events at constituent phytomers. Some data have been presented for numbers of leaf primordia on the upper portion of the tiller axis (Sharman 1947;Wilman et al 1994), but we are unaware of published counts of numbers of roots per node or phytomer at lower positions on tiller axes.…”
mentioning
confidence: 99%